Vulnerability among rural older adults in southern Brazil: population-based study - Tatiane Gonzalez; Cristina Paludo; Rodrigo Meucci (Rural and Remote Health, 2023)
Introduction: The study aimed to estimate the prevalence of vulnerability, and to identify the associated factors of vulnerability among rural community-dwelling older adults living in the municipality of Rio Grande, Rio Grande do Sul, Brazil. Methods: This was a cross-sectional, population-based study of a sample of individuals aged 60 years or older. Data from the first follow-up of the EpiRural Cohort Study (2018-2019) were used. Vulnerability was assessed using the Vulnerable Elders Survey (VES-13). The maximum score is 10 and older adults with scores of 3 or more are classified as vulnerable. Poisson regression with robust adjustment of variance was used for crude and adjusted analyses. For the analysis of the associated factors, a theoretical model was constructed with three hierarchical levels. The variables were adjusted in relation to each other within each level; those with a significance level of 0.20 or less were included in the regression model and adjusted to a higher level, with a subsequent level of significance of 5%. Results: The overall prevalence of vulnerability was 40.8% (95%CI 37.5-44.3). Vulnerability was more prevalent among women (PR=1.45; 95%CI 1.23-1.71), older adults who did not work (PR=1.70; 95%CI 1.17-2.45), those who lived without a partner (PR=1.26; 95%CI 1.07-1.47), those with diabetes (PR=1.23; 95%CI 1.03-1.48), those with depression (PR=1.21; 95%CI 1.02-1.42), those with osteoporosis (PR=1.38; 95%CI 1.15-1.66), and those with sarcopenia (PR=1.67; 95%CI 1.38-2.02). Conclusion: Vulnerability is common among rural community-dwelling older adults and is associated with sociodemographic and health characteristics.